2010
DOI: 10.1177/0886260510369135
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrative Theoretical Framework for Explaining Beliefs About Wife Beating: A Study Among Students of Nursing From Turkey

Abstract: An integrative theoretical framework was tested as the basis for explaining beliefs about wife beating among Turkish nursing students. Based on a survey design, 406 nursing students (404 females) in all 4 years of undergraduate studies completed a self-administered questionnaire. Questionnaires were distributed and collected from the participants during their attendance of core courses. The results revealed that between 8% and 27% of the students expressed some level of willingness to justify wife beating, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
2
11
2
3
Order By: Relevance
“…Aggression against women, particularly wife beating and related justifying attitudes, is a complex, multidimensional issue, and an extensive body of past studies has shown that one theory is not sufficient to explain justifying attitudes nor actual aggressive behavior (cf., Haj-Yahia & Uysal, 2011;Heise, 1998). Hence, there is a need to combine different theoretical perspectives into an integrative framework because this may allow a more elaborate understanding of the complex phenomena of wife beating attitudes.…”
Section: Theoretical Framework and Predictors Of Wife Beating Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggression against women, particularly wife beating and related justifying attitudes, is a complex, multidimensional issue, and an extensive body of past studies has shown that one theory is not sufficient to explain justifying attitudes nor actual aggressive behavior (cf., Haj-Yahia & Uysal, 2011;Heise, 1998). Hence, there is a need to combine different theoretical perspectives into an integrative framework because this may allow a more elaborate understanding of the complex phenomena of wife beating attitudes.…”
Section: Theoretical Framework and Predictors Of Wife Beating Attitudesmentioning
confidence: 99%
“…First, we studied predictors of wife beating attitudes that are based on three theoretical perspectives. As no single theory can completely explain justification of wife beating (Haj-Yahia & Uysal, 2011;Heise, 1998), we examined theoretically-relevant predictors within an integrative theoretical framework, comprising patriarchal ideology, social learning theory, and social cognitions. Second, we followed a gender-inclusive approach examining attitudes toward wife beating among both adolescent girls and boys.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This further emphasizes the influence of traditional and patriarchal views that seeking outside help for wife abuse is perceived as disruptive to the cohesiveness of the family, particularly as it is related to the collectivist and patriarchal nature of Arab society. Studies in other collectivist societies have shown similar effect of attitudes toward women and marital role expectations on acceptance of helping battered women (Haj-Yahia & Sadan, 2008;Haj-Yahia & Shen, 2015;Haj-Yahia & Uysal, 2011). For example, among South Asian immigrant women in Canada, women reported delaying seeking help due to social stigma, rigid gender roles, marriage obligations, and the expectation that women should keep silence about family matters (Ahmad et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, individuals internalize, learn, and modify new attitudes and behaviors through a process of modeling. It has been consistently argued that reinforcement of modeling serves to enhance the vicarious learning of new attitudes and behavior through observation of the consequences of others’ attitudes and behaviors, as well as through direct experience (Haj-Yahia & Uysal, 2011; Markowitz, 2001). In this study, we examine how witnessing father-to-mother violence, experiencing parental violence, and knowing a woman who has been physically assaulted by her husband are related to the participants’ attitudes toward the interventions of social workers in cases of wife assault.…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%
“…There are various obstacles and barriers that can prevent health practitioners from becoming involved in detecting victims of domestic violence and from performing the above-mentioned tasks that are expected of them in their work with battered women. Those obstacles and barriers include: traditional attitudes and misconceptions about abuse and violence, fear of invading individual privacy, discomfort talking with battered women, fear of offending the women, a sense of powerlessness, exclusive emphasis on physical health, limited formal education, lack of professional knowledge and skills for dealing with cases of domestic violence, shortage of supportive facilities and services, and the feeling that identification of abuse and violence is not part of their role (Berkowitz, 2005; Haj-Yahia & Uysal, 2011; Han, 2008; McCauley, Jenckes, & McNutt, 2003). Other obstacles that prevent health practitioners from becoming involved in detecting cases of domestic violence include infrequent patient visits, patients’ unresponsiveness to the practitioner’s questions about domestic violence, the practitioner’s lack of time, and the patient’s lack of response to referrals (Haj-Yahia & Uysal, 2011).…”
mentioning
confidence: 99%